Clinical and biochemical characteristics in patients with polycystic ovary syndrome and infertility - Quillatupa Valencia, Norka (2015)
Objective: To describe the most important clinical and biochemical characteristics in patients with polycystic ovary syndrome (PCOS) treated for infertility. Design: Observational, descriptive, retrospective study. Setting: Service of Human Reproduction and Infertility, Hospital Nacional Arzobispo Loayza, Lima, Peru. Participants: Patients with diagnosis of infertility and PCOS. Interventions: Between January 1995 and December 2007, 5640 clinical histories were reviewed, 181 patients had diagnosis of infertility and PCOS, and 59 met the admission criteria. Main outcome measures: Pregnancy and abortion. Results: Mean age was 27,5; 70% of the population not achieving pregnancy had a body mass index ≥ 25; testosterone was high in 15% of successful pregnancies and in 37,5% of the unsuccessful ones; 74,2% patients ovulated with clomiphene citrate, 52,4% achieved pregnancy and 16,7% presented miscarriage. Conclusions: Many clinical and  biochemical characteristics of our population are similar to those described in the literature. A normal body mass index would be a good clinical marker to predict conception. Testosterone value in normal range may be a possible predictor of success at pregnancy.